CONSPIRITUALITY CAPITALISM: YOGA, AUTHENTICITY, AND WHITENESS ON A STREAMING VIDEO PLATFORM - Eadon, Yvonne (AoIR Selected Papers of Internet Research, 2023)
Entering “best online yoga classes,” into Google Search returns lists from fitness websites like VeryWell Fit, Yogi Times, Prevention, Self, and Shape—most of these sites will include Gaia.com, a subscription-based streaming video platform, in their recommendation lists, labeling it variously as “best for the whole family,” “best intermediate/advanced,” and, most notably, “best for delving into yogic philosophy.” None of the blurbs written about Gaia in these articles mention its thousands of videos about conspiracy theories. These articles also fail to mention the connection between Gaia and Gaiam, one of the largest global yoga equipment brands. Formerly GaiamTV, Gaia.com offers videos and articles about yoga alongside videos and articles about UFOs, extraterrestrials, alternative archaeology, and universal consciousness, among a variety of other topics related to conspiracy theories, the paranormal, and new age spirituality. This paper examines Gaia, Inc., as a case study in conspirituality capitalism. The blatant obfuscation of the connection between Gaiam yoga equipment and the Gaia media empire functions to strengthen the mechanisms of conspirituality capitalism: not only are supporters of conspiratorial and alternative content financially contributing to its production through subscriptions to Gaia, but yoga practitioners who purchase Gaiam equipment may be unknowingly supporting Gaia’s conspiritual content. Using qualitative, grounded-theory-informed content analysis of video and textual content hosted on the site, as well as participant observation at two Gaia conferences held at the GaiaSphere Event Center outside Denver, Colorado, this paper, which is exploratory in nature, will introduce the term conspirituality capitalism and examine Gaia as a case study in it.